The 2013 protests and the emergence of a new right in Brazil - Borges, Carlos Eduardo de Assis (Seven Editora, 2024)
This study provides a comprehensive analysis of the protests that occurred in June 2013 in Brazil and their impact on the country’s political landscape. Initially, the protests were contextualized within a backdrop of social inequalities, corruption, and widespread dissatisfaction with the current political system. The Free Fare Movement (MPL) emerged as a symbol of this mobilization, driven by popular outrage and decentralized organization facilitated by social media. The narrative of a new right gained prominence, characterized by a rejection of traditional politics and corruption. The research aimed to review existing literature on these events, investigating triggering factors, conducting an analysis of anti-political discourse, and assessing implications for Brazilian democracy. Through a methodology that included academic sources, scientific articles, and political analyses, the aim was to provide a comprehensive understanding of the political dynamics that shaped contemporary Brazil, reflecting on the challenges and opportunities for the country’s future. DOI:https://doi.org/10.56238/sevened2024.010-021